Global observations of reflectors in the mid-mantle with implications for mantle structure and dynamics - Lauren Waszek (Nature Portfolio, 2018)
The Earth’s mantle undergoes changes as temperature and pressure increase with depth. Here, the authors present a global interrogation of reflectors in the Earth’s mid-mantle revealing a significant variation in their properties, with widespread compositional heterogeneity and seismic velocity in the mid-mantle, which signify contrasting styles of mantle flow.